Intrinsic Motivation Inventory : Psychometric properties in the context of first language and mathematics learning - Monteiro, Vera (2015)
Intrinsic Motivation Inventory (IMI) is a multidimensional measurement grounded on the Self-Determination Theory (SDT) used in assessing the subjective experiences of participants when developing an activity. The aim of this study is to analyze the characteristics of IMI among Portuguese students, testing four organizational models (unidimensional, multidimensional, hierarchical and bi-factor). A total of 3685 students from the 5th to the 12th grades (50.4% boys) participated in the study (M = 13.67, SD = 2.26). Two versions of IMI were used (First Language and Mathematics) with twenty-one items distributed over five subscales: Enjoyment, Perceived Competence, Pressure/ Tension, Perceived Choice and Value/Utility. The confirmatory factor analysis corroborated the multidimensionality of intrinsic motivation, and that the bi-factor model presented the best fit indexes. This model showed the existence of one general factor, resulting from the contribution of all individual dimensions and the particularities of most of them. Furthermore, results also highlighted satisfactory reliability scores both through Cronbach’s alpha scores and Composite reliability scores. These results indicate that this scale is appropriate to evaluate the underlying constructs of the theoretical model of SDT and allows for the calculation of a global measure of intrinsic motivation, as well as specific measures for their predictors.